Village Fund Policy Based Planning Development - Siti Hajar; Kholilul Kholik; Nur Ambia Arma (Iapa Proceedings Conference, 2022)
Village funds are used for village development through the development of village potential as an effort to increase PAD and the community's economy, including the establishment of BUMDes which aims to manage village assets and can open new job opportunities for village communities. This village fund also requires dedication from the village government but because of the limited capacity of human resources as village fund managers and village heads. Acceleration of village development with the use of village funds can be carried out by utilizing area-based village funds that lead to natural resource management adapted to rural settlements, government services, social services, and economic activities so that village potentials and problems can be mapped and resolved in perspective more comprehensive. The method used in this study is the Participatory Rural Appraisal (PRA) method. This research produces a form of synergistic participation in developing village potential through village fund policies that must be managed and can provide benefits to the community so that it can encourage the realization of village independence and at the same time integrate village potential with all parties, namely the government, community, private sector.